Hydrophobicity Analysis of Protein Primary Structures to Identify Helical Regions - Pattini, L.; Cerutti, S. (Methods of Information in Medicine, 2004)
Objectives: A wavelet based approach for the hydrophobicity analysis of protein primary structures is proposed to predict the presence of alpha helices in the secondary structure.Methods: The information about hydropathy profile periodicity content together with a score of probability of occurrence of a single amino acid allows the localization of alpha helices.Results: The accuracy is comparable to other consolidated predictors based on different techniques (i.e.: neural networks, hidden markov models).Conclusion: This method is particularly suitable to capture the amphiphilic character of the helical structures.
Keywords: Protein sequence; secondary structure; hydrophobicity; alpha helix; wavelet transform